Standoff Raman Detection of Explosive Materials Using a Small Raman Spectroscopy System - Hadi, Naseer M; Mohammad, Mohammad R; Abdulzahraa, Haider G (Al-Nahrain Journal of Science, 2017)
In this work a standoff Raman spectroscopy SRS system has been designed, assembled and tested for detecting explosives (Ammonium nitrate, Trinitrotoluene and Urea nitrate) in dark laboratory at 4 m target-telescope distance. The SRS system employs frequency doubled Nd:YAG laser at 532 nm excitation with laser power of 250 mW and integration time of 2 second. The Cassegrain telescope was coupled to the Ventana Raman spectrometer using a fiber optics cable, and Notch filter is used to reject Rayleigh scattering light. The Raman scattered light is collected by a telescope and then transferred via fiber optic to spectrometer and finally directed into charge coupled device CCD detector. In order to test SRS system, it has been used to detect the Raman spectra of Toxic Industrial Compounds TIC such as acetone, toluene, and carbon tetrachloride. The SRS results were compared with conventional Raman microscopy results using a bench top Bruker SENTERRA Raman instrument.